The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.20944/preprints201705.0207.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are spatial planning objectives reflected in the evolution of urban landscape patterns? A framework for the evaluation of spatial planning outcomes

Abstract: Abstract:The evaluation of spatial planning results, or outcomes, has been rather neglected by scholars and practitioners. The causes of this neglect are linked to the characteristics of the planning systems in use or difficulties in quantifying results. To advance the state of the art of outcome evaluation, this paper focuses on assessing the implementation of national spatial planning objectives in urban landscapes, through the use of an evaluation framework that makes use of spatially explicit information. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 38 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…A more generalized understanding of the effects of institutional factors on land-use change is, however, a prerequisite to transfer knowledge on effective growthmanagement approaches. There is, thus, a need for more international comparative research that reflects the specific political, social or cultural context of the successful management of urban expansion (see e.g., Grădinaru, Iojă, Pătru-Stupariu and Hersperger (2017) and Pagliarin (2018)). Against this background, the analytical model of "regional governance capacities" has been proven useful in empirical studies (see Dang, Visseren-Hamakers and Arts (2016)).…”
Section: Effectiveness Of Growth Managementmentioning
confidence: 99%
“…A more generalized understanding of the effects of institutional factors on land-use change is, however, a prerequisite to transfer knowledge on effective growthmanagement approaches. There is, thus, a need for more international comparative research that reflects the specific political, social or cultural context of the successful management of urban expansion (see e.g., Grădinaru, Iojă, Pătru-Stupariu and Hersperger (2017) and Pagliarin (2018)). Against this background, the analytical model of "regional governance capacities" has been proven useful in empirical studies (see Dang, Visseren-Hamakers and Arts (2016)).…”
Section: Effectiveness Of Growth Managementmentioning
confidence: 99%
“…The conformance approach generally considers plans as blueprints, with their provisions eventually reflected in actual spatial development (Laurian et al, 2004;Mastop and Faludi, 1997;Talen, 1997). Consequently, this approach assumes that plans are successfully implemented if (1) their policies are executed (Lyles et al, 2016) and/or (2) if outcomes on the ground correspond to plan provisions (Alexander and Faludi, 1989;Gra˘dinaru et al, 2017;Loh, 2011;Oliveira and Pinho, 2010;Talen, 1996). Recently, Lyles et al (2016) suggested using the term conformance when assessing whether policies are carried out, the term influence when assessing whether a plan is used in decision-making and performance when addressing whether a plan influences outcomes.…”
Section: Measuring Plan Implementationmentioning
confidence: 99%
“…Different planning activities should be supervised to ensure they comply with the objectives, which leads to the development of different methodologies on this topic [10].…”
Section: Introductionmentioning
confidence: 99%